2018
DOI: 10.1016/j.amjoto.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Total intravenous versus inhaled anesthesia in transsphenoidal tumor surgery

Abstract: Our study shows no evidence that total intravenous anesthesia is superior to inhaled anesthesia or vice versa during endoscopic transsphenoidal sinus surgery with regard to relevant clinical outcome parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…Sixth, we did not compare clinically important outcomes, such as intraoperative hemodynamics and recovery profiles from anesthesia, between sevoflurane and propofol groups. However, previous studies showed no clinically significant differences in terms of perioperative hemodynamics, intraoperative thermoregulation and blood loss, time to extubation, length of stay in the post‐anesthesia recovery room, and operating conditions between sevoflurane and propofol anesthesia for ETS 23‐27 . Lastly, the non‐inferiority margin was as high as 9% in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…Sixth, we did not compare clinically important outcomes, such as intraoperative hemodynamics and recovery profiles from anesthesia, between sevoflurane and propofol groups. However, previous studies showed no clinically significant differences in terms of perioperative hemodynamics, intraoperative thermoregulation and blood loss, time to extubation, length of stay in the post‐anesthesia recovery room, and operating conditions between sevoflurane and propofol anesthesia for ETS 23‐27 . Lastly, the non‐inferiority margin was as high as 9% in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…20 Despite this data, studies have been inconclusive due to variable TIVA infusion rates/doses decreasing the reliability of the results. 29 Additionally, nomograms and available cerebral monitors, such as bispectral index (BIS) monitoring, utilized for intravenous anesthesia can create variation for serum and cerebral concentrations for propofol. A recent Cochrane review noted a large number of RCTs showing that general anesthesia with BIS had earlier recovery time and decreased risk of intraoperative awareness when compared to anesthesia without BIS.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, in studies by Fish et al and Gollapudy et al, no difference in recovery room time between TIVA and inhaled anesthesia was shown. 16,17 Finally, an article by Gupta et al suggested that early recovery times were shorter with inhaled anesthetics and not TIVA. 18 Thus, the literature is in disagreement on these time-based parameters, and further study is needed to understand when TIVA or inhaled anesthetics are advantageous for the patient.…”
Section: Discussionmentioning
confidence: 99%